DEVELOPMENT POP-UP BOOK: A LEARNING MEDIA TO REDUCE FOOD LOSS AND FOOD WASTE IN JUNIOR HIGH SCHOOL STUDENTS - Martini; Catur Surya Saputra; Ardiansyah Dharma Syahputra; Eva Lestari; Vyra Garmyta Utamy (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2024)
The development of interesting learning media needs to be done to attract students' interest. Food loss and food waste are quite serious problems because the effects of food loss and food waste are very detrimental to humans. One of the learning media that can be developed as an educational effort related to the problem of food waste and food loss, namely pop-up books. The purpose of this study was to determine the results of the validity, effectiveness, and practicality of pop-up books to train students to reduce food loss and food waste. The research design used research and design (R&D). The participants in this study were class VII in one of the Surabaya city junior high schools in the Even Semester 2021/2022. The instruments used in the study, namely: feasibility test instruments for media experts, media feasibility test instruments for material experts, food loss and food waste literacy questions, and response questionnaires. Data collection techniques, namely: written tests, observations and surveys with paper & pencil. Data analysis techniques for validity use a Likert scale by finding the average, effectiveness is analyzed using Normalized change, and practicality is analyzed using a response questionnaire by finding the percentage of each indicator. The results of this study, material expert validators obtained a percentage of 90% and media expert validators obtained a percentage of 93%. The effectiveness of this media obtained a score of <c> = 0.67 with the interpretation of moderate improvement. The practicality of this media obtained a percentage of 93% with a very good interpretation. Pop-up book food loss and waste is a feasible media to be used in learning to train and reduce food loss and food waste.